Application of Multimodal Navigation together with Fluorescein Angiography in Microsurgical Treatment of Cerebral Arteriovenous Malformations. Issue 1 (December 2017) - Feng, Shiyu; Zhang, Yanyang; Sun, Zhenghui; Wu, Chen; Xue, Zhe; Ma, Yudong; Jiang, Jinli
Abstract This study aimed to explore the clinical applications of multimodal navigation combined with indocyanine green (ICG) fluorescein angiography in microsurgical treatment of cerebral arteriovenous malformations (AVMs). We retrospectively collected 52 patients with AVMs. Assisted by anatomic image, we reestablished three-dimensional structure using preoperative functional magnetic resonance imaging (fMRI) and Diffusion tensor imaging (DTI). The operation for lesion resection was finished under the assistance of neuro-navigation. ICG fluorescein angiography was performed for 16 of the study subjects, meanwhile, FLOW800 was used to rebuild blood vessel color visual image. Brain angiography was performed 1 week after the operation to check residual malformations. The patients' status was estimated by Modified Rankin Scale score. Of the AVMs, 92.3% (48/52) were totally removed, without severe side events. Among the patients, fluorescein angiography was carried out up to 58 times for 16 cases. All of these 16 cases were confirmed with malformations and 14 of them had draining vein. The total resection rate of these 16 cases reached 100%, and the occurrence rate of postoperative complications was not significantly increased. During the operation of lesion resection, the application of multimodal navigation could effectively protect functional cortex and conduction pathway.